Pengaruh Berbagai Bahan Litter Terhadap Konsentrasi Ammonia Udara Ambient kandang dan Performan Ayam Broiler - Sulaiman Ibrahim; Allaily Allaily (Agricultural Faculty, 2012)
The effect of different litter materials on ammonia concentration of the air ambient stall and broiler performanceABSTRACT. The study was conducted to observe the effect of ammonia concentration of broiler chicken coop air to the treatment various types of litter. High ammonia concentrations would interfere with performance of broiler chickens and become a problem for the environment. A good litter quality is expected to address the problem of ammonia that occur in the broiler chicken coop. This study uses a completely randomized, with 5 litter treatments. T0 without treatment repose only black plastic as litter, litter composition T1 100% bran, 50% T2 litter composition husks and Charcoal Shell 50%, T3 50% 50% husk litter composition and zeolite 50%, T4 25% husks litter composition, 25% charcoal, 25% zeolite and 25% of the land. Each treatment was repeated 3 times, each test consisted of eight chickens. Parameters observed in the form of ammonia concentration of air cages at week four, weekly feed intake, weight gain per week, the final weight, feed conversion, and mortality. The results indicate different types of litter treatment was very real influence of ammonia concentration of air enclosure. T4 treatment with a 1:1 blend of each component of the litter that is used successfully absorb such a large aerial ammonia, which indicates the ammonia content of the air is the smallest compared with other treatment 4. While the treatment without litter showed a very large aerial ammonia compared with the treatment. Feed consumption results also showed that the treatment that produces a small value causes ammonia to be markedly higher consumption. Values for weight gain, final weight, feed conversion, and mortality are not significantly affected by various types of litter treatment.